Drivers of Mobile Health Acceptance and Use From the Patient Perspective - Salgado, Tânia (2020)
Salgado, T., Tavares, J., & Oliveira, T. (2020). Drivers of Mobile Health Acceptance and Use From the Patient Perspective: Survey Study and Quantitative Model Development. JMIR mHealth and uHealth, 8(7), e17588. https://doi.org/10.2196/17588